Changes in supramolecular structure and improvement in reactivity of dissolving pulp via enzymatic pretreatment with processive endoglucanase EG1 from Volvaria volvacea. (3rd May 2020) - Wu, Shanshan; Zhang, Yuemei; Jiang, Xiao; Wang, Shulei; Liu, Jiang; Wu, Shufang
Abstract: Processive endoglucanase EG1 and its core domain, EG1(CD), were used to pretreat the commercial dissolving pulp to improve cellulose reactivity. The Fock reactivity of the pulp which was treated with EG1 and EG1 (CD) at 50 U/g enzyme loading increased from 74.3% of the control to 90.6% and 88.4%, respectively. Refining also improved the Fock reactivity of the pulp, but not as effective as EG1 or EG1(CD) treatment. Refining prior to EG1 or EG1(CD) treatment could slightly further improve the Fock reactivity, to 91.6% and 90.0%, respectively. After enzymatic treatment and (or) refining, the water retention value, differential scanning calorimetry and alkaline solubility analysis indicated that enzyme treatment, especially by EG1, significantly increased the accessibility of fibers to reaction reagents. Combined with the characteristics of soluble reducing sugar produced by EG1 treatment and the changes of degree of polymerization, it is inferred that a small fraction of cellulose crystallization regions are destroyed in the enzymatic hydrolysis process due to the processive acting ability of EG1, and some microchannels in the fiber cell wall were created, which is similar to the effect of "drilling holes", so that the reaction reagent can reach the inside of the cell wall evenly, thus obviously improving the reactivity of the dissolved pulp.